IMPROVING THE ABILITY OF JOB INTERVIEWS IN ENGLISH FOR VOCATIONAL SCHOOL CADETS USING THE DEMONSTRATION METHOD - Siti Julaihah (Jurnal Penelitian)
This study discusses the readiness of cadets in facing the job interview process in English where the demands from companies or agencies are that they have reliable and professional personnel. In the initial activity of recruiting employees, there are several stages that must be met in addition to the administrative requirements, the HR is also required to be able to carry out the interview process well, especially in English. The research method used in this research is classroom action research which is carried out in two cycles in the first cycle, the researcher uses the direct instruction method and in the second cycle uses the demonstration method. The results of this study arebased on the achievement of the success criteria at the end of cycle 2 where the average value of the cadets reached 80.13. In addition, the percentage of the number of cadets who got a score of 71 reached 100%.